Antidepressant but Not Prophylactic Ketamine Administration Alters Calretinin and Calbindin Expression in the Ventral Hippocampus - LaGamma, Christina T.; Tang, William W.; Morgan, Ashlea A.; McGowan, Josephine Cecelia; Brachman, Rebecca A.; Denny, Christine A. (Frontiers in Molecular Neuroscience, 2018)
Ketamine has been found to have rapid, long-lasting antidepressant effects in treatment-resistant patients with major depressive disorder (MDD). Recently, we have also shown that ketamine acts as a prophylactic to protect against the development of stress-induced depressive-like behavior in mice, indicating that a preventative treatment against mental illness using ketamine is possible. While there is significant investigation into ketamine’s antidepressant mechanism of action, little is known about ketamine’s underlying prophylactic mechanism. More specifically, whether ketamine’s prophylactic action is molecularly similar to or divergent from its antidepressant action is entirely unknown. Here, we sought to characterize immunohistochemical signatures of cell populations governing ketamine’s antidepressant and prophylactic effects. 129S6/SvEv mice were treated with saline (Sal) or ketamine (K) either before a social defeat (SD) stressor as a prophylactic, or after SD as an antidepressant, then subsequently assessed for depressive-like behavior. Post-fixed brains were processed for doublecortin (DCX), calretinin (CR), and calbindin (CB) expression. The number of DCX+ neurons in the dentate gyrus (DG) of the hippocampus (HPC) was not affected by prophylactic or antidepressant ketamine treatment, while the number of CR+ neurons in the ventral hilus increased with antidepressant ketamine under SD conditions. Moreover, antidepressant, but not prophylactic ketamine administration significantly altered CR and CB expression in the ventral HPC. These data show that while antidepressant ketamine treatment mediates some of its effects via adult hippocampal markers, prophylactic ketamine administration does not, at least in 129S6/SvEv mice. These data suggest that long-lasting behavioral effects of prophylactic ketamine are independent of hippocampal DCX, CR, and CB expression in stress-susceptible mice.